New insights into the genetic diversity, phylogeny, and immunogenic potential of the wsp gene in Wolbachia endosymbionts in Brugia malayi and Brugia pahangi - Witchuta Junsiri; Piyanan Taweethavonsawat (Current Research in Parasitology and Vector-Borne Diseases)
Wolbachia spp. are intracellular, maternally inherited bacteria that infect a wide range of arthropods. These bacteria influence reproductive traits in their hosts and are used in mosquito-borne virus control programmes. This study investigates the Wolbachia surface protein (WSP), a potential trigger of innate immune responses. The wsp gene was amplified by polymerase chain reaction, cloned, and sequenced. Phylogenetic analysis showed that wsp sequences from Wolbachia endosymbionts of Brugia pahangi and B. malayi formed two clades within the supergroup D. The wsp sequences were highly conserved, with 99–100% sequence identity across global isolates. Haplotype analysis revealed 13 distinct wsp haplotypes. The average antigenic score of the WSP protein was 1.029 for B. malayi and 1.026 for B. pahangi. MHC-NP analysis predicted eight antigen ligands for B. malayi and six for B. pahangi. Notably, a shared antigen ligand (VIADQKHGF) was identified for both species, associated with dog leukocyte antigens (DLA-8850101, DLA-8803401, and DLA-8850801). Additionally, a conserved ligand region (ALVMLLSLSNSAFSD) was identified in the WSP of B. malayi, corresponding to human leukocyte antigens (HLA-DR alleles HLA-DRB1∗04:04 and HLA-DRB1∗04:01). These findings provide new insights into the phylogenetic classification, sequence conservation, and immunogenic potential of the WSP protein in Wolbachia endosymbionts of Brugia spp.